Bovine Holo-Beta-Lactoglobulin Cross-Protects Against Pollen Allergies in an Innate Manner in BALB/c Mice: Potential Model for the Farm Effect - Afify, Sheriene Moussa (Front Immunol, 2021)
The lipocalin beta-lactoglobulin (BLG) is a major protein compound in cow’s milk, and we detected it in cattle stable dust. BLG may be a novel player in the farm protective effect against atopic sensitization and hayfever. In previous studies, we demonstrated that only the ligand-filled holo-form of BLG prevented sensitization to itself. Here, we investigated whether holo-BLG could, in an innate manner, also protect against allergic sensitization to unrelated birch pollen allergens using a murine model. BALB/c mice were nasally pretreated four times in biweekly intervals with holo-BLG containing quercetin–iron complexes as ligands, with empty apo-BLG, or were sham-treated. Subsequently, mice were intraperitoneally sensitized two times with apo-BLG or with the unrelated birch pollen allergen apo-Bet v 1, adjuvanted with aluminum hydroxide. After subsequent systemic challenge with BLG or Bet v 1, body temperature drop was monitored by anaphylaxis imaging. Specific antibodies in serum and cytokines of BLG- and Bet v 1-stimulated splenocytes were analyzed by ELISA. Additionally, human peripheral blood mononuclear cells of pollen allergic subjects were stimulated with apo- versus holo-BLG before assessment by FACS. Prophylactic treatment with the holo-BLG resulted in protection against allergic sensitization and clinical reactivity also to Bet v 1 in an unspecific manner. Pretreatment with holo-BLG resulted in significantly lower BLG-as well as Bet v 1-specific antibodies and impaired antigen-presentation with significantly lower numbers of CD11c+MHCII+ cells expressing CD86. Pretreatment with holo-BLG also reduced the release of Th2-associated cytokines from Splenocytes in BLG-sensitized mice. Similarly, in vitro stimulation of PBMCs from birch pollen allergic subjects with holo-BLG resulted in a relative decrease of CD3+CD4+ and CD4+CRTh2 cells, but not of CD4+CD25+CD127− Treg cells, compared to apo-BLG stimulation. In conclusion, prophylactic treatment with holo-BLG protected against allergy in an antigen-specific and -unspecific manner by decreasing antigen presentation, specific antibody production and abrogating a Th2-response. Holo-BLG therefore promotes immune resilience against pollen allergens in an innate manner and may thereby contribute to the farm protective effect against atopic sensitization.